Animating Discipline Disparities through Debilitating Practices: Girls of Color and Inequitable Classroom Interactions. Issue 5 (May 2020) - Annamma, Subini Ancy; Handy, Tamara; Miller, Amanda L.; Jackson, Elizabeth
Context: Girls of Color are overrepresented in school disciplinary actions based on subjectively judged, minor infractions. Studies have consistently shown that this exclusionary discipline has long-lasting impact on Girls of Color and their educational outcomes, including increased risk for pushout and involvement in the criminal legal system. Focus of Study: We sought to uncover the processes that animate the statistics of overrepre-sentation of Girls of Color in disciplinary actions. Said differently, we sought to understand where, how, and why Girls of Color were being disciplined in schools. Using a Disability Critical Race Theory (DisCrit) lens and centering the voices of Girls' of Color, this empirical study was guided by the question, What mechanisms propel and dispel disciplinary inequities for Girls of Color? Research Design: The qualitative research took place in a suburban school district in the Midwestern United States marked by increasing racial, cultural, and linguistic diversity. This was part of a larger two-year study that centered the voices of more than 50 Girls of Color, their families (11), and their teachers (11), exploring understandings of and experiences with school discipline disparities for Girls of Color. Data sources for the full project included interviews with Girls of Color (32), families (10), and teachers (8); focus groups (Girls of Color = 17; families = 3; teachers = 3); classroom and district event observations, Education Journey Mapping (21); and a Cartographer's Clinic. Data for this study focus on the interviews and focus groups with Girls of Color, working to center them as knowledge generators. Conclusions/Recommendations: Our analysis revealed the ways in which discipline disparities were animated by inequitable academic and behavioral responses of teachers to classroom interactions, which we name debilitating practices. Further, Girls of Color embodied repositioning as ways of maintaining their integrity and individuality when experiencing academic and behavioral injustices. We conclude with major implications for school personnel: (a) academically, educators must reflect on how ability is distributed and withheld in the classroom along racialized and gendered lines, and (b) behaviorally, positive behavior supports should be imagined and implemented through a race and gender conscious lens. Though we focus on classroom interactions, we also understand that public schools, schools of education, and society all have a role to play in dismantling the school–prison nexus. However, classroom interactions continue to be identified as the source of disciplinary disparities in both quantitative and qualitative studies. Consequently, teachers have an opportunity to change their classroom practices to academically and behaviorally support Girls of Color.